Rethinking Slave Rebellion in Cuba : La Escalera and the Insurgencies of 1841-1844 - Finch, Aisha K. (Book collections on Project MUSE., 2015)
Envisioning La Escalera - an underground rebel movement largely composed of Africans living on farms and plantations in rural western Cuba - in the larger context of the long emancipation struggle in Cuba, Aisha Finch demonstrates how organised slave resistance became critical to the unraveling not only of slavery but also of colonial systems of power during the nineteenth century.